An improved protocol to study the plant cell wall proteome - Printz, Bruno; Dos Santos Morais, Raphaël; Wienkoop, Stefanie; Sergeant, Kjell; Lutts, Stanley; Hausman, Jean-Francois; Renaut, Jenny (Frontiers in Plant Science, 2015)
Cell wall proteins were extracted from alfalfa stems according to a 3-steps extraction procedure using sequentially CaCl2, EGTA and LiCl-complemented buffers. The efficiency of this protocol for extracting cell wall proteins was compared with the 2 previously published methods optimized for alfalfa stem cell wall protein analysis. Following LC-MS/MS analysis the 3-steps extraction procedure resulted in the identification of the highest number of cell wall proteins (242 NCBInr identifiers) and gave the lowest percentage of non-cell wall proteins (about 30%). However, the 3 protocols are rather complementary than substitutive since 43% of the identified proteins were specific to one protocol. This 3-step protocol was therefore selected for a more detailed proteomic characterization using 2D-gel electrophoresis. With this technique, 75% of the identified proteins were shown to be fraction-specific and 72.7% were predicted as belonging to the cell wall compartment. Although being less sensitive than LC-MS/MS approaches in detecting and identifying low-abundant proteins, gel-based approaches are valuable tools for the differentiation and relative quantification of protein isoforms and/or modified proteins. In particular isoforms, having variations in their amino-acid sequence and/or carrying different N-linked glycan chains were detected and characterized. This study highlights how the extracting protocols as well as the analytical techniques devoted to the study of the plant cell wall proteome are complementary and how they may be combined to elucidate the dynamism of the plant cell wall proteome in biological studies. Data are available via ProteomeXchange with identifier PXD001927.